Alpha Fetoprotein as a Marker of Severe Disease and Foetal Outcome in Pregnancy Induced Hypertension - Olumodeji, Ayokunle Moses; Adewara, Olumide Emmanuel; Adeyemo, Olabisi Timothy; Ghazali, Segun Murtala; Olowoyo, Paul (International Journal of Innovative Research in Medical Science, 2019)
Background: Pregnancy-induced hypertension represents the most common medical complication of pregnancy and contributes significantly to maternal and neonatal morbidity and mortality. Many theories have been implicated in its genesis, crucial among which is the defective 2nd wave of trophoblastic invasion/placentation. Maternal serum alpha fetoprotein is a marker of placental abnormalities and may correlate with clinical features of significant management implications. This study evaluated the role of maternal Alpha-fetoprotein concentration as a marker of disease severity and foetal outcome in patients with pregnancy induced hypertension at the Federal Teaching Hospital, Ido-Ekiti, Ekiti state, Nigeria. Methodology: This was a prospective study in which 44 patients with PIH and 88 matched controls that satisfied the inclusion criteria were recruited using convenience sampling technique for cases and systematic random sampling for controls. Relevant socio-demographic, maternal medical and obstetric characteristics, alpha-fetoprotein levels and fetal outcome measures were obtained. A p-value of less than 0.05 was considered statistically significant. SPSS 20.0 statistical package (SPSS Inc, Chicago, IL, USA) was used for statistical analysis. Results: The prevalence of PIH in the study was 15.3%. The difference in the mean (±2SD) serum level of alpha fetoprotein (AFP) between the cases (207±156.2ng/ml) and control group (165.2±115.1ng/ml) was not statistically significant (p=0.079). The mean (±2SD) birth weight of babies born to women with PIH in this study was 2.7±0.6kg which was significantly lower (p<0.001; 95%CI 3.0 – 3.1)) than the mean birth weights of 3.2±0.4kg of babies of normotensive controls. The mean (± 2SD) Apgar scores at both 1 minute and 5 minutes were both significantly lower in the PIH group (6.7±1.8 and 8.4±1.5 respectively) than among the normotensive women (7.6±1.2 and 8.9±1.1 respectively). Thirty-one point eight percentage of babies born to women in the PIH group and 11.4% of babies of normotensive controls required admission into special care baby unit (SCBU) (Odds Ratio=1.17; 95%CI (0.24-5.76) Serum AFP had a reasonable negative correlation with both birth weight (r=-0.47, p=0.001) and Apgar score at 5 minute (r=-0.44, p=0.002). At 2 MoM serum AFP level, sensitivity and specificity for severe PIH were 36% and 90% respectively. Conclusion: Maternal serum AFP levels showed reasonable positive correlation with disease severity and adverse fetal outcome that warrants further investigation. Maternal serum AFP can be useful in identifying pregnant women with PIH at risk of having severe disease and adverse foetal outcome.